ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN NEGARA BUKAN PAJAK (PNBP) PADA LEMBAGA KEPOLISIAN (DIREKTORAT LALU LINTAS POLDA NTT) SEBELUM PANDEMI DAN PADA MASA PANDEMI - Clara Margilia Reinamah (JAKA - Jurnal Jurusan Akuntasi, 2022)
The purpose of this study was to measure the level of effectiveness and contribution of Non-Tax Revenue at the Directorate of Traffic East Nusa Tenggara, National Police of the Republic of Indonesia before the pandemic and during the pandemic. The method used in this research is descriptive quantitative. Data collection techniques used in this research are document studies and literature studies, while data analysis techniques use effectiveness ratio analysis with the output in the form of contributions made to state revenues. The results show that the level of effectiveness of Non-Tax Revenue in the period before pandemic, namely in 2019 was classified as ineffective with a ratio of 67.4%, and the level of effectiveness in 2020 during the Covid 19 pandemic was also ineffective with a ratio of 62.2%. The largest contribution rate of Non-Tax revenue during the pandemic in 2019 was generated from the BPKB component with a percentage of 48% and the lowest was from regional mutations with a percentage of 0.39%, while during the pandemic in 2020 the largest contribution was from STNK with a percentage of 35.34% and the lowest from the mutation area is 0.75%. This is influenced by the weakening of the community's economy due to the pandemic due to job losses due to the pandemic. The recommendation that can be given to the Traffic Directorate is to improve performance by providing socialization to the public about the importance of paying Non-tax revenue so that the target can be achieved, the Directorate must provide Strict sanctions for vehicle users who do not pay their obligations